Age as a Prognostic Factor in Anaplastic Thyroid Cancer. (15th June 2014) - Zivaljevic, Vladan; Tausanovic, Katarina; Paunovic, Ivan; Diklic, Aleksandar; Kalezic, Nevena; Zoric, Goran; Sabljak, Vera; Vekic, Berislav; Zivic, Rastko; Marinkovic, Jelena; Sipetic, Sandra
Abstract : Background. Anaplastic thyroid cancer (ATC) is one of the tumors with the shortest survival in human medicine. Aim. The aim was to determine the importance of age in survival of patients with ATC. Material and Methods . We analyzed the data on 150 patients diagnosed with ATC in the period from 1995 to 2006. The Kaplan-Meier method and log-rank test were used to determine overall survival. Prognostic factors were identified by univariate and multivariate Cox regression analysis. Results. The youngest patient was 35 years old and the oldest was 89 years old. According to univariate regression analysis, age was significantly associated with longer survival in patients with ATC. In multivariate regression analysis, patients age, presence of longstanding goiter, whether surgical treatment is carried out or not, type of surgery, tumor multicentricity, presence of distant metastases, histologically proven preexistent papillary carcinoma, radioiodine therapy, and postoperative radiotherapy were included. According to multivariate analysis, besides surgery (P = 0.000, OR = 0.43, 95% CI = 0.29–0.63), only patients age (P = 0.023, OR = 0.68, 95% CI = 0.49–0.95) was independent prognostic factor of favorable survival in patients with ATC. Conclusion . Age is a factor that was independently associated with survival time in ATC. Anaplastic thyroid cancer has the best prognosis in patients younger than 50 years.